Cover Image, Volume 15, Issue 2. (11th May 2017) - Azakami, D.; Nakahira, R.; Kato, Y.; Michishita, M.; Kobayashi, M.; Onozawa, E.; Bonkobara, M.; Kobayashi, M.; Takahashi, K.; Watanabe, M.; Ishioka, K.; Sako, T.; et al.
Abstract : The cover image, by D. Azakami et al., is based on the Original Article The canine prostate cancer cell line CHP‐1 shows over‐expression of the co‐chaperone small glutamine‐rich tetratricopeptide repeat‐containing protein α, DOI: 10.1111/vco.12199 . Abstract : The cover image, by D. Azakami et al., is based on the Original Article The canine prostate cancer cell line CHP‐1 shows over‐expression of the co‐chaperone small glutamine‐rich tetratricopeptide repeat‐containing protein α, DOI: 10.1111/vco.12199 .